Adjuvant Chemoradiotherapy Versus Adjuvant Chemotherapy for Stage III Gastric or Gastroesophageal Junction Cancer After D2/R0 Resection - Shi, Jinming; Kang, Wenzhe; Tang, Yuan; Li, Ning; Jiang, Liming; Yang, Lin; Wang, Shulian; Song, Yongwen; Liu, Yueping; Fang, Hui; Lu, Ningning; Qi, Shunan; et al. (Frontiers in Oncology, 2022)
Purpose To compare the survival benefit in the adjuvant chemoradiotherapy (CRT) group and chemotherapy (CT) group for stage III gastric or gastroesophageal junction (GEJ) cancer after D2/R0 resection. Methods and Materials From January 2011 to May 2018, 819 patients (CRT group: 215 patients, CT group: 604 patients) diagnosed as pathological stage III after D2/R0 resection were retrospectively collected and the survival and recurrence patterns were analyzed. The baseline characteristics were balanced based on propensity score matching (PSM). The survival benefit was compared between two groups using Kaplan–Meier analysis and Cox regression model. Results The 5-year overall survival (OS) rate in the CRT group was significantly higher than that in the CT group whether before or after the PSM. The multivariate Cox regression analysis identified the significant poor OS in patients with advanced TNM stage (P < 0.001) and patients who did not receive the adjuvant CRT (P = 0.008). For the recurrence patterns, 85 (39.5%) patients in the CRT group and 300 (49.7%) patients in the CT group were diagnosed as recurrence (P = 0.011). The regional recurrence in the CRT group was less than that in the CT group (20.5% vs. 35.1%, P = 0.028). Conclusion For patients diagnosed as stage III gastric cancer or gastroesophageal junction cancer, the addition of adjuvant chemoradiotherapy will significantly improve the overall survival and regional control.